Anaphylactic Reaction During Implantation of the Ovation Stent-Graft System in a Patient With Abdominal Aortic Aneurysm. (August 2015) - Sfyroeras, George S.; Moulakakis, Konstantinos G.; Antonopoulos, Constantine N.; Manikis, Dimitris; Vasdekis, Spyridon N.
Purpose: To describe a case of anaphylactic reaction during implantation of the Ovation Abdominal Stent Graft System in a patient treated for abdominal aortic aneurysm (AAA).Case Report: An 82-year-old man with a 5.3-cm asymptomatic AAA underwent endovascular repair using an Ovation stent-graft. Polymer was infused into the inflatable rings of the aortic body under continuous angioscopy, but the rings were not filled, even though the entire amount of the polymer was administered. Simultaneously, the patient presented with a severe anaphylactic reaction resulting in cardiopulmonary arrest. He was successfully resuscitated, but the procedure was abandoned; the patient refused any further treatment.Conclusion: A rupture of the Ovation main body's polymer-filled rings may lead to extremely severe anaphylactic reaction.